Case Study 8: The Censorship Crisis: Response 1 - Gregory, Jess L. (Educational Leadership in Action, 2015)
This chapter presents a complex, real-life, accessible case study in expecting the best to provoke and stimulate conversation around practical problems and alternative solutions that confront educational leaders today. These cases cover a wide range of topics, including: teacher evaluations, educational reforms, school safety, cultural differences, undocumented students, and social media. Each case study has three alternative responses written by experienced educational administrators and academics. The respondents were asked to identify the primary problem, along with secondary problems to provide a strategy that will address the problems identified. The chapter starts with an observation that, over time, any supervisor who moves up the chain of responsibility experiences much, and usually begins to formulate empirically derived rules. The organization and unique approach of Educational Leadership in Action allows for flexible use in courses for aspiring leaders to supplement core readings, reinforce central concepts, exemplify theory, and provide grounded examples to encourage learning.
Num Pages: 1
Keywords: dept.edl